GPCR-dependent pathways promote nanodomain-specific cAMP signaling in human cardiomyocytes, which is severely remodeled in atrial fibrillation. (10th June 2022) - Beneke, K; Grammatika Pavlidou, N; Schaefer, A; Reichenspurner, H; E Molina, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft, German Centre for Cardiovascular Research (DZHK) Background: Cardiac arrhythmias, such as atrial fibrillation (AF), have been linked to the remodeling of membrane receptors and alterations in cAMP-dependent regulation of calcium handling mechanisms. For instance, decreased L-type calcium channel (LTCC) current density but upregulated ryanodine receptor 2 (RyR2) are major hallmarks of AF. Furthermore, adenosine A2A receptor (A2AR) stimulation increases calcium waves without affecting LTCC and serotonin (5-HT) receptors activation exerts stronger control over myofilaments than over RyR2 function. However, up to date no study has elucidated how the increase on cAMP upon different G-protein-coupled receptors (GPCR) stimulation can lead to different physiological compartmentalized responses. The aim of this study was to investigate the effects of various GPCRs on cAMP levels in different cellular compartments in human atrial myocytes from control patients in sinus rhythm (Ctl), and how these compartmentalized effects are altered in AF. Furthermore, alterations in downstream cAMP level control by phosphodiesterases (PDEs) between patient groups were investigated to further elucidate functional differences. Methods: Atrial myocytes were isolated from tissues of 66 AF and 80 Ctl patients. Cells were then transduced with adenoviruses (Epac1-camps, pm-Epac1-camps and Epac1-JNC) and cultured for 48 hours to express the Förster-resonance energy transfer (FRET)-based cAMP sensor in the cytosolic, membrane and RyR2 nanodomains, respectively. FRET was then used to measure cAMP in 532 isolated human atrial myocytes. Stimulation with β-adrenergic agonist Isoprenaline (ISO, 100nM) was used and compared with 5-HT (100µM) and A2AR (with CGS, 200nM) stimulation. Additionally, a nonspecific PDE inhibitor (IBMX, 100µM) was applied, as well as PDE3 (Cilostamide, 1µM) and PDE4 (Ro 20-1724, 10µM) specific inhibitors. Results: A desensitization to β-adrenergic receptor stimulation in AF myocytes was exclusively found in the cytosol, while no difference was seen in neither the RyR2 nor LTCC compartment in AF versus Ctl. Similar effects were observed upon 5-HT stimulation with a significant desensitization in the cytosol, and no difference in the RyR2 compartment. On the contrary, AF myocytes displayed a significantly higher increase in cAMP levels compared to Ctl myocytes in the cytosol upon A2ARs stimulation. Importantly, no effect on cAMP levels was observed in the LTCC compartment after A2ARs or 5-HT stimulation. However, PDE3 inhibition on top of 5-HT stimulation showed a significantly smaller effect on cAMP levels in AF myocytes within the LTCC compartment. Conclusions: Collectively, our data show that cAMP levels are highly compartmentalized in human atrial myocytes and differentially regulated by different GPCRs. Furthermore, PDEs are to a certain extent responsible for the compartmentalized effects of the different GPCRs.